2015
DOI: 10.1186/s12883-015-0288-2
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive impairment six months after ischaemic stroke: a profile from the ASPIRE-S study

Abstract: BackgroundCognitive impairment commonly occurs in the acute phase post-stroke, but may persist with over half of all stroke survivors experiencing some form of long-term cognitive deficit. Recent evidence suggests that optimising secondary prevention adherence is a critical factor in preventing recurrent stroke and the incidence of stroke-related cognitive impairment and dementia. The aim of this study was to profile cognitive impairment of stroke survivors at six months, and to identify factors associated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
143
0
11

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 182 publications
(168 citation statements)
references
References 50 publications
(54 reference statements)
6
143
0
11
Order By: Relevance
“…According to the result of this study, it was found that the memory disturbance between 20 -80 percentage 7,8 and the incidence of dementia after stroking was 5 -48%. 3,4,[11][12][13][14][15][16] Moreover, the incident of dementia after recurrent stroke was 33.33 %.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…According to the result of this study, it was found that the memory disturbance between 20 -80 percentage 7,8 and the incidence of dementia after stroking was 5 -48%. 3,4,[11][12][13][14][15][16] Moreover, the incident of dementia after recurrent stroke was 33.33 %.…”
Section: Discussionmentioning
confidence: 68%
“…4 From the previous study that traced patients with stroke during three months it was found that most patients have mild disability (57.2%), some have severe disability (18.6%), and a few have moderate disability (9.4%). 5 In addition, stroke also led to memory disturbance and dementia over 9.4 times compared with and without stroke, 6 memory disturbance between 20 -80 percentage, 7,8 and the incidence of dementia was 5-48 percentage. 3,4 Moreover, probability of recurrent stroke increased, 9,10 recurrent stroke was 33.3 percentage, 11 the mortality rate of dementia after stroking was three times compared with and without, 7 and the estimated cost of caring the dementia patients around the world is approximately 604,000 million US dollar.…”
Section: Introductionmentioning
confidence: 99%
“…Sin embargo, la evidencia cualitativa sobre la experiencia de sobrevivientes de ACV señala la necesidad de considerar, para la atención, categorías relacionadas con la interrupción biográfica (cambio, transición, transformación), las pérdidas, el aislamiento social, la adaptación y la reconciliación, más que sobre la enfermedad en sí misma, e invitan a no dejar de lado la discapacidad residual neurológica del sobreviviente de ACV y señalan cómo una revisión sistemática con metaanálisis demostró que el 10 % de pacientes pueden desarrollar demencia en el año posterior al primer ACV (3,18,19).…”
Section: Discussionunclassified
“…Quienes sobreviven al ACV pueden padecer discapacidad física o cognitiva, problemas visuales, problemas de comunicación, disminución de la sensibilidad, pérdida de la conciencia de una parte de su cuerpo, limitación en las actividades con secuelas por varios años (3,4). Después de la fase aguda, los sobrevivientes regresan a casa con importantes limitaciones.…”
Section: Introductionunclassified
“…Из 256 пациентов больше чем у половины (у 56,6%) обнаружены когнитивные нарушения различной степени выраженности, при этом лечение антигипертензивными препаратами и антикоагулянтная терапия были связаны с уменьшением риска развития когнитивных нарушений [23]. Важным является и кон-троль других наиболее значимых факторов риска: сер-дечно-сосудистой патологии, сахарного диабета, гипер-липидемии, гипергомоцистеинемии.…”
Section: неврологияunclassified